Impact of AI Dependency on Faculty Research Creativity and Critical Thinking in Higher Education Institutions (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Artificial Intelligence has rapidly become an integral component of academic research and higher education practices. Faculty members increasingly rely on AI-assisted technologies for scholarly writing, literature exploration, data analysis, and idea development. Although these digital tools improve efficiency and accessibility in research activities, excessive dependence on AI-generated assistance may influence originality, reflective thinking, and independent academic judgment. The present study explores the relationship between AI dependency, research creativity, and critical thinking among faculty members in higher education institutions. A descriptive quantitative approach was adopted, and primary data were collected from 50 respondents through a bilingual Likert-scale questionnaire. Statistical techniques including correlation, regression, mean score analysis, and ANOVA were used to interpret the findings. The results indicate that AI technologies positively support research productivity and creative idea generation; however, overreliance on automated outputs may reduce deep analytical engagement and originality. The study highlights the need for ethical, balanced, and responsible integration of AI technologies in academic research environments.